Development of SNPs and their use for the identification of summer mortality resistance QTLs in the Pacific oyster (Crassotrea gigas) - Sauvage, Christopher; Lapegue, Sylvie; Bierne, Nicolas; Boudry, Pierre (International Association for Genetics in Aquaculture (IAGA), 2006)
Summer mortalities of the Pacific cupped oyster Crassostrea gigas have been described in the literature for decades. One solution to overcome this problem would be to select animals more tolerant to summer mortalities, as this trait was shown to be highly heritable (Degrémont, 2003). The identification of markers associated to the resistance would allow to better understand this complex phenomenon and, eventually to establish markers assisted selection. Recently, two moderately dense genetic linkage maps have been established in the Pacific oyster based on microsatellites and AFLP markers (Hubert and Hedgecock, 2004; Li and Guo, 2004). In this context, the development and mapping of SNPs will increase the density of the linkage map and consequently the accuracy of QTL mapping. To reach this objective, crosses between "resistant" and "sensitive" mapping parents (F0) was performed in 2003 to generate F1 families. Segregating F2 families will be produced in 2006 for SNP mapping and QTL analyses. The development of SNPs is in progress. We identify SNPs by the direct sequencing of ESTs. Our first results show a high level of polymorphism (from 1 to 5 SNPs / 100 bp) and only 3% of the EST are monomorphic. Each SNP will be scored by mass spectrometry to validate each marker and to detect heterozygote loci in F1 and F2 progenies.